The Vertebrate biodiversity of the Gigantes and Sicogon Islands, Iloilo Province, Philippines - Bucol, Abner A.; Alcala, Ely L.; Averia, Leonardo; Cordova, Lirio (2010)
The biodiversity of the Gigantes and Sicogon Islands and associated islets are presented and discussed based on a study conducted from December 2009 to May 2010. Pertinent data on the biophysical conditions of caves in the Gigantes are also presented. Observations on the biology of the Critically Endangered Gigante Limestone Frog ( Platymantis insulatus) and the Endangered Gigante Narrow-disked Gecko (Gecko gigante) such as population density, behaviour, and reproductive biology are also presented. Threats to the biodiversity of these islands are discussed with corresponding recommendations. A preliminary discussion on the zoogeography of the two islands is also provided.
Keywords: Biodiversity; Zoogeography; Islas de Gigantes (Iloilo)